Neonatal Outcomes of Elective Early-term Births After Demonstrated Fetal Lung Maturity. Issue 2 (February 2019) - Tita, Alan T. N.; Jablonski, Kathleen A.; Bailit, Jennifer L.; Grobman, William A.; Wapner, Ronald J.; Reddy, Uma M.; Varner, Michael W.; Thorp, John M.; Leveno, Kenneth J.; Caritis, Steve N.; Iams, Jay D.; Saade, George; et al.
Abstract : (Abstracted from Am J Obstet Gynecol 2018;219(3):296.e1–296.e8) Studies of early-term birth after demonstrated fetal lung maturity show that respiratory and other outcomes are worse with early-term birth (37 0/7–38 6/7 weeks) even after demonstrated fetal lung maturity when compared with full-term birth (39 0/7–40 6/7 weeks). However, these studies included medically indicated births and are therefore potentially limited by confounding by the indication for delivery.